2019
DOI: 10.1038/s41598-019-46375-6
|View full text |Cite
|
Sign up to set email alerts
|

A Plant-Produced in vivo deglycosylated full-length Pfs48/45 as a Transmission-Blocking Vaccine Candidate against malaria

Abstract: Pfs48/45 is a leading antigen candidate for a transmission blocking (TB) vaccine. However, efforts to produce affordable, safe and correctly folded full-length Pfs48/45 using different protein expression systems have not produced an antigen with satisfactory TB activity. Pfs48/45 has 16 cysteines involved in disulfide bond formation, and the correct formation is critical for proper folding and induction of TB antibodies. Moreover, Pfs48⁄45 is not a glycoprotein in the native hosts, but contains potential glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…The stability analysis of plant produced glycosylated and Endo H in vivo deglycosylated forms of RBD and gS1 of SARC-CoV were examined after incubation at 37 °C for 48, 96, 72 and 96 hours. The procedure of stability analysis was similar to those described previously 21 .These analyses showed that dRBD degradation was very low at incubation at 37 ° C for 24 hours (less than 10 %), however, at the same condition, gRBD degraded significantly (more than 60%).…”
Section: Stability Assessment Of Rbd Variants and S1mentioning
confidence: 78%
See 2 more Smart Citations
“…The stability analysis of plant produced glycosylated and Endo H in vivo deglycosylated forms of RBD and gS1 of SARC-CoV were examined after incubation at 37 °C for 48, 96, 72 and 96 hours. The procedure of stability analysis was similar to those described previously 21 .These analyses showed that dRBD degradation was very low at incubation at 37 ° C for 24 hours (less than 10 %), however, at the same condition, gRBD degraded significantly (more than 60%).…”
Section: Stability Assessment Of Rbd Variants and S1mentioning
confidence: 78%
“…The stability analysis of plant produced gRBD, dRBD and gS1 of SARS-CoV-2 recombinant proteins were examined after incubation at 37 °C for 48, 96, 72 and 96 hours using similar procedure as described previously 21 . Protein samples were diluted to 0.5 mg/ mL with PBS and were transferred into polypropylene Eppendorf low-binding tubes.…”
Section: Stability Assessment Of Plant Produced Rbd Variants and S1prmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is challenging to produce functionally active antigens and associated with incorrect folding of some complex proteins (especially proteins with many disulfide bridges) produced in different host expression system. Therefore, for production of functionally active protein antigens more flexible approaches are required (Mamedov et al 2012;Mamedov et al 2017;Mamedov et al 2019a).…”
Section: Modern-protein Based Vaccinesmentioning
confidence: 99%
“…The problem has recently been addressed through the development of an economical and practical technology that provided production of proteins of interest in native-like, non-glycosylated forms. This was achieved by in vivo deglycosylation of target proteins of interest by co-expression with bacterial PNGase F (Mamedov et al 2012;Mamedov and Yusibov 2013;Mamedov et al 2016) or with Endo H enzymes (Mamedov et al 2017;Mamedov et al 2019b).Using this technology, a functional active Pfs48/45 antigen of Plasmodium falciparum has been produced in plants and mice immunized with this antigen showed strong inhibition in standard membrane-feeding assay (SMFA) analysis for the first time (Mamedov et al 2019a and b). This technology has been also applied for production of protective antigen of Bacillus anthracis (Mamedov et al 2012;Mamedov et al 2016;Mamedov et al 2017;Mamedov et al 2019a).…”
Section: Plant Expression System: Advantages Limitations and Solutionsmentioning
confidence: 99%